A Bioinspired Light‐Controlled Ionic Switch Based on Nanopipettes. Issue 4 (6th February 2015) - Li, Ting; He, Xiulan; Yu, Ping; Mao, Lanqun; Rees, Neil V.
Abstract Development of new principles for fabrication of novel ionic devices has attracted much attention due to the potential applications of ionic devices in molecular computer, biosensing and electronic circuit. Inspired by optogenetics altering membrane voltage via light‐controlled proteins, a new kind of light‐controlled ionic switch was demonstrated here based on nanopipettes. Upon exposure to visible light, spiropyran (SP) does not coordinate with Zn2+, resulting in a relatively large ionic current. While, upon UV light irradiation, SP was transformed into merocyanine (MC) that coordinates with Zn2+ and thereby results in the decrease in the ionic current. The ionic current could be reversibly modulated by UV/Vis light irradiation. The finite‐element simulation was performed to understand the possible mechanism underlying the light‐controlled ionic switch based on nanopipettes.